Analiza ekonomiczna polskiej reformy emerytalnej z 2013 r. - Sieroń, Arkadiusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The aim of this paper is to conduct an economic analysis of the Polish pension reform of 2013. We claim that the changes implemented, although they did not entail nationalization (as was commonly believed) significantly reduced, if not abolished, the major part of the pensions system. On this ground, we consider the choice between ZUS and OFE practically irrelevant
Keywords: system zabezpieczenia społecznego; emerytury; fundusze emerytalne; reforma emerytalna; ZUS; OFE; FUS; otwarte fundusze emerytalne; system emerytalny; Polska